AKTIVITAS ANTIOKSIDAN PADA SEDIAAN KOMBUCHA BUNGA TELANG YANG DIRACIK DARI FORMULASI GULA AREN DAN MADU SR12 SEBAGAI PRODUK BIOTEKNOLOGI PANGAN DAN FARMASI - Rezaldi, Firman; Utami, Arti Wahyu; Resti Wijayanti, Fitria Eka; Purbanova, Reni; Wati, Dyah Rohma; Suminar, Erny; Kusumiyati, Kusumiyati; Mu’jijah, Mu’jijah; Faizah, Nai’matul Retno; Cahyono, Andri Tri; Setyaji, Diyan Yunanto; Fadillah, M Fariz; Yenny, Ratna Fitry (Program Studi Agribisnis Fakultas Pertanian, 2024)
The food and pharmaceutical fields are two elements needed in everyday life to improve human health and well-being. This is because functional foods, medicines, and natural cosmetics have become an increasingly current trend to be applied both based on food biotechnology and pharmaceutical biotechnology. One of the food and pharmaceutical biotechnology products that can be effective as a source of antioxidants is the butterfly pea flower kombucha preparation. Butterfly pea flower kombucha preparations that are effective as a source of antioxidants certainly have a substrate formula that varies based on the results of their concoctions. The results of previous studies have proven that butterfly pea flower kombucha with a concentration of palm sugar and SR12 honey has activity as a source of antibacterial. Research to see the antioxidant activity that is formulated based on various formulations of palm sugar and SR12 honey substrates. The stages of this research include making butterfly pea flower kombucha with various concentrations of palm sugar and SR12 honey substrates and testing its antioxidant activity on each preparation formulated from the palm sugar and SR12 honey substrate formulation (20%, 30%, and 40%). One-way analysis of variance was applied, followed by post-hoc analysis. Based on the post-hoc analysis, the study showed that butterfly pea flower kombucha at a concentration of 40%, as well as the formula of palm sugar and SR12 honey, showed significant differences from the concentrations of 20% and 30% after testing one-way analysis of variance, with each P value <0.05. The conclusion is that the preparation of butterfly pea flower kombucha based on the use of palm sugar and SR12 honey substrates is efficacious as a source of antioxidants so that in the long term it can be used as a functional food ingredient or pharmaceutical.